Contributive roles of multilevel organizational learning for the evolution of organizational ambidexterity. Issue 3 (1st August 2016) - Yan, Mengling; Yu, Yan; Dong, Xiaoying
Abstract : Purpose: – The purpose of this paper is to reveal how organizational learning at the strategic and operational levels (i.e. strategic learning and business learning, respectively) contribute to the development of organizational ambidexterity along the growth of enterprises from an evolutionary view. Design/methodology/approach: – The authors conducted a longitudinal single case study on Huawei – a leading Chinese firm in the telecommunication industry. Data were collected from various sources including interviews, senior speeches, scholarly publications, company magazines and other documents, and was analyzed in line with the principles of grounded theory. Findings: – This research reveals that the case company (Huawei) constructed organizational ambidexterity with different foci during different development stages. The organization's ambidextrous capability evolves over time, shifting from one domain to another. Such ambidexterity development was largely beneficial from the multilevel organizational learning at both the strategic level (focussing on the whole organization and long-term goals) and operational level (focussing on local interests and short-term goals). Originality/value: – This paper represents one of the earliest works to uncover the ambidexterity building process from an evolutionary approach that requires the collection of longitudinal data. Also, the paper proposes a multi-level learning framework for ambidexterity building in practice. This framework distinguishes strategic learning from business learning and projects the two types of learning into learning at four levels-individual, team, intra-organizational, and inter-organizational, which can be leveraged to guide division of labor among hierarchical levels during the progressive development of ambidexterity.